2018
DOI: 10.1111/jocs.13828
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of ≥5-year mortality in randomized controlled trials of off-pump versus on-pump coronary artery bypass grafting

Abstract: Objectives We sought to determine whether off‐pump coronary artery bypass grafting (CABG) increases long‐term mortality, by performing a meta‐analysis of randomized controlled trials (RCTs) of off‐pump versus on‐pump CABG with ≥5‐year follow‐up. Methods MEDLINE and EMBASE, and the Cochrane Central Register of Controlled Trials were searched through July 2018. Hazard, risk, or odds ratios (HRs, RRs, or ORs) of long‐term (≥5‐year) mortality for off‐pump versus on‐pump CABG were extracted from each individual tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…For example, on-pump CABG is associated with a higher risk of perioperative stroke than OPCABG (beating heart CABG), though the latter is usually reserved for selected higher risk patients, due to higher technical difficulty. 7,[29][30][31] Predictive models for stroke risk following CABG based on readily available clinical variables have been proposed and validated. 32,33…”
Section: Risk Factorsmentioning
confidence: 99%
“…For example, on-pump CABG is associated with a higher risk of perioperative stroke than OPCABG (beating heart CABG), though the latter is usually reserved for selected higher risk patients, due to higher technical difficulty. 7,[29][30][31] Predictive models for stroke risk following CABG based on readily available clinical variables have been proposed and validated. 32,33…”
Section: Risk Factorsmentioning
confidence: 99%
“…79 Clinical Evidence: OPCAB Versus On-Pump CABG OPCAB has evolved as an alternative to on-pump CABG, with multiple randomized controlled trials demonstrating comparable outcomes (Table 2). 16,17,42,[80][81][82][83] However, there still is considerable debate as to the relative efficacy of OPCAB as it compares with traditional on-pump CABG. From numerous trials and large retrospective studies, it is reasonable to deduce that OPCAB reduces postoperative morbidity at the expense of higher rates of incomplete revascularization.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…85 However, several recent randomized controlled trials have reported increased 5-year mortality for OPCAB on long-term follow-up. 17,83,86,87 This likely is owing to the worse long-term graft patency with increased rates of graft occlusion and the need for subsequent revascularization in OPCAB patients. 42,79,81,82 However, a recent post hoc analysis using a large propensity-matched subset from the Arterial Revascularization Trial showed no difference in 5-year mortality for OPCAB versus on-pump CABG.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…In recent years, off-pump coronary artery bypass grafting (OPCABG) has been widely used in the surgical treatment of coronary heart disease. OPCABG without using a cardiopulmonary artery bypass (CPB) can present the influence of extracorporeal circulation on the human body, may present a number of complications, such as post-procedure myocardial, pulmonary, renal and cerebral complications, and better protect the coagulation mechanism, but may increase the risk of postoperative thrombosis (1)(2)(3). It is known that the postoperative graft of vascular stenosis and occlusion eventually leads to serious cardiovascular events, such as myocardial ischemia and myocardial infarction, which result in increased patient mortality.…”
Section: Introductionmentioning
confidence: 99%